Change in fatty acid composition of plasma triglyceride caused by a 2 week comprehensive risk management for diabetes: A prospective observational study of type 2 diabetes patients with supercritical fluid chromatography/mass spectrometry‐based semi‐target lipidomic analysis. Issue 1 (8th October 2022) - Taya, Naohiro; Katakami, Naoto; Omori, Kazuo; Hosoe, Shigero; Watanabe, Hirotaka; Takahara, Mitsuyoshi; Miyashita, Kazuyuki; Nishizawa, Hitoshi; Konya, Yutaka; Obara, Sachiko; Hidaka, Ayako; Nakao, Motonao; et al.
Abstract: Aims/Introduction: Hypertriglyceridemia is common in patients with diabetes. Although the fatty acid (FA) composition of triglycerides (TGs) is suggested to be related to the pathology of diabetes and its complications, changes in the fatty acid composition caused by diabetes treatment remain unclear. This study aimed to identify short‐term changes in the fatty acid composition of plasma triglycerides after diabetes treatment. Materials and Methods: This study was a sub‐analysis of a prospective observational study of patients with type 2 diabetes aged between 20 and 75 years who were hospitalized to improve glycemic control ( n = 31). A lipidomic analysis of plasma samples on the 2nd and 16th hospital days was conducted by supercritical fluid chromatography coupled with mass spectrometry. Results: In total, 104 types of triglycerides with different compositions were identified. Most of them tended to decrease after treatment. In particular, triglycerides with a lower carbon number and fewer double bonds showed a relatively larger reduction. The inclusion of FA 14:0 (myristic acid), as a constituent of triglyceride, was significantly associated with a more than 50%, and statistically significant, reduction (odds ratio 39.0; P < 0.001). The total amount of FA 14:0 as a constituent of triglycerides also decreased significantly, and its rate of decrease was the greatest of all the fatty acid constituents. Conclusions: A 2 week comprehensive risk management for diabetes resulted in decreased levels of plasma triglycerides and a change in the fatty acid composition of triglycerides, characterized by a relatively large reduction in FA 14:0 as a constituent of triglycerides. Abstract : Although the fatty acid (FA) composition of triglycerides (TGs) is suggested to be related to the pathology of diabetes and its complications, changes in FAs composition caused by diabetes treatment remain unclear. This study aimed to identify short‐term changes in the FA composition of plasma TGs after comprehensive diabetes treatment. A 2‐week comprehensive diabetes treatment resulted in decreased levels of plasma TGs and a change in the FAs composition of TG, characterized by a relatively large reduction in FA 14:0 as a constituent of TGs.